“What’s our escape plan, and where are we going to meet up?”: Theorising platform evacuation in platform society - Annabell, Taylor; Abidin, Crystal (AoIR Selected Papers of Internet Research, 2026)
This paper develops the analytical framework of “platform evacuation” to explore the dynamics of collective departure and migration of users from a social media platform due to a crisis in or of platform governance. Drawing on internet research addressing platform governance, platform cultures, creator practices, and digital memory work, we theorise “platform evacuation” as grounded in changes to governance by platforms or governance on platforms and requiring strategic management of a community across experiences of disruption, uncertainty and loss. Influencers, creators, and mainstream celebrities demonstrate evacuation leadership through public announcements of departure, commemorations of nostalgia and loss, and negotiations of community migration, reconfiguring existing practices as well as developing specific tactics to navigate the urgency, precarity and politics of crisis. “Platform evacuation” is oriented towards identifying and understanding strategies, performances, and narratives used to manage both voluntary or forced withdrawal from connective networks that users depend upon for work, interaction, and daily life. Our account of evacuation practices across the temporal unfolding of the 2025 US TikTok ban illustrates the stages of platform evacuation: creators explained the politics of evacuation through memetic content, engaged in platform remembrance and mourning, encouraged community migration and performed curtain calls. Thinking with temporalities, spatialities and discourses of platform evacuation, we propose, allows for a critical examination of collective departures and migrations from social media platforms as anticipated, instigated, and negotiated.